LGBT psychology and mental health emerging research and advances - Ruth, Richard; Santacruz, Erik (Santa Barbara, California Praeger, an imprint of ABC-CLIO, LLC, 2017)
"This book presents emerging discoveries, trends, and research areas in LGBT psychology, both in science and therapy. It brings together concise, substantive reviews of what is new or on the horizon in science and in key areas of clinical practice, and provides information and insight to help psychologists, mental health clinicians, and counselors better serve the LGBT populations that, increasingly, are seeking their services"--Publisher's description.
1. Introduction: Why This Book and What You Can Expect / Richard Ruth and Erik Santacruz -- 2. New Developments in LGBT Development : what's (still) true / Stephen L. Forssell -- 3. Making psycholotgy trans-inclusive and trans-affirmative : recommendations for resarch and practice / Riddhi Sandil and Shane Henise -- 4. How contemporary psychoanalysis contributes to LGBT psychology : examining and addressing gender fluidty and diversity as we slide toward 21st-centuy transformations / Shara Sand 5. LGBT Psychology and Ethnic Minority Perspectives : Intersectionality / Barbara C. Wallace and Erik Santacruz -- 6. Intersectional Feminism and LGBTIQQA+ Psychology : Understanding Our Present by Exploring Our Past / Deanna N. Cor and Christian D. Chan -- 7. Caught at the Intersections : Microaggressions toward Lesbian, Gay, Bisexual, Transgender, and Queer People of Color / Kevin L. Nadal ... [et al.] -- 8. Addictions and Substance Abuse in the LGBT Community : New Approaches / Barbara C. Wallace and Erik Santacruz -- 9. Health Disparities and LGBT Populations / Barbara C. Wallace and Erik Santacruz -- 10. Challenges in Moving toward the Resolution, Reduction, and Elimination of Health Disparities for LGBT Populations / Barbara C. Wallace and Erik Santacruz -- 11. LGBT Health and LGBT Psychology : Emerging Policy Issues / Ronald L. Schlittler ... [et al.] -- 12. Quality and Equality : An Interdisciplinary Graduate Program to Develop Agents of Change in LGBT Health / Stephen L. Forssell ... [et al.] -- 13. Going Forward : Summary and New Directions / Richard Ruth and Erik Santacruz.
Karl Cosido (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Sexual minorities -- Mental health; Sexual minorities -- Psychology; Sexual and Gender Minorities -- psychology; Mental Health